Origin and diversification of the plasminogen activation system among chordates - Chana-Muñoz, Andrés (BMC Evol Biol, 2019)
BACKGROUND: The plasminogen (PLG) activation system is composed by a series of serine proteases, inhibitors and several binding proteins, which together control the temporal and spatial generation of the active serine protease plasmin. As this proteolytic system plays a central role in human physiology and pathophysiology it has been extensively studied in mammals. The serine proteases of this system are believed to originate from an ancestral gene by gene duplications followed by domain gains and deletions. However, the identification of ancestral forms in primitive chordates supporting these theories remains elusive. In addition, evolutionary studies of the non-proteolytic members of this system are scarce. RESULTS: Our phylogenetic analyses place lamprey PLG at the root of the vertebrate PLG-group, while lamprey PLG-related growth factors represent the ancestral forms of the jawed-vertebrate orthologues. Furthermore, we find that the earliest putative orthologue of the PLG activator group is the hyaluronan binding protein 2 (HABP2) gene found in lampreys. The prime plasminogen activators (tissue- and urokinase-type plasminogen activator, tPA and uPA) first occur in cartilaginous fish and phylogenetic analyses confirm that all orthologues identified compose monophyletic groups to their mammalian counterparts. Cartilaginous fishes exhibit the most ancient vitronectin of all vertebrates, while plasminogen activator inhibitor 1 (PAI-1) appears for the first time in cartilaginous fishes and is conserved in the rest of jawed vertebrate clades. PAI-2 appears for the first time in the common ancestor of reptiles and mammals, and represents the latest appearing plasminogen activator inhibitor. Finally, we noted that the urokinase-type plasminogen activator receptor (uPAR)—and three-LU domain containing genes in general—occurred later in evolution and was first detectable after coelacanths. CONCLUSIONS: This study identifies several primitive orthologues of the mammalian plasminogen activation system. These ancestral forms provide clues to the origin and diversification of this enzyme system. Further, the discovery of several members—hitherto unknown in mammals—provide new perspectives on the evolution of this important enzyme system. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12862-019-1353-z) contains supplementary material, which is available to authorized users.